Correlation between the Level of Knowledge and Attitude Regarding Early Marriage among Female High School Students - Yunita Eriska; Fitri Fujiana; Suhaimi Fauzan (Poltekkes Kemenkes Palu, 2023)
The rate of early marriage in West Kalimantan in 2018 occupied the 14th place with a percentage of 21.22%, while in 2020 it increased to 24%. A study conducted at Kubu Raya District in 2014, showed that there were 63.6% of 88 prospective brides in the work area of Sungai Kakap Community Health Center who experienced unwanted pregnancies. The results of the Program Performance and Accountability Survey (SKAP) in 2019 showed that 63 out of 1,000 women in the age range of 15-19 years had given birth. This problem is also related to the incidence of unwanted pregnancies in West Kalimantan which reached 23.4% as reported in the 2019 SKAP survey data. This study aims to identify and analyze the correlation between the level of knowledge and attitude related to early marriage among female students at SMAN 1 of Sungai Kakap. This was a quantitative study using the cross sectional method. The study samples were selected using purposive sampling technique which obtained 81 respondents. The data collection instruments applied here were a questionnaire related to the level of knowledge regarding early marriage and a questionnaires related attitude regarding early marriage. The data collected were analyzed based on the frequency distribution and statistical test of the Spearman correlation test. The study findings based on the Spearman test obtained a significance value or p-value=0.000 (<0.005) and the correlation coefficient value of 0.556. Someone with a good level of understanding about early marriage would also have good character or an unsupportive attitude regarding underage marriage. Thus, it can be concluded that there was a significant correlation between the level of knowledge and attitude regarding early marriage among female students at SMAN 1 of Sungai Kakap. It is expected that the study finding can be applied as a guide for conducting further research, especially regarding the correlation between the level of knowledge and attitude regarding early marriage among female adolescents, as well as the basis for community service.